New Technologies for the Understanding, Assessment, and Intervention of Emotion Regulation - Colombo, Desirée; Fernández-Álvarez, Javier; García Palacios, Azucena; Cipresso, Pietro; Botella, Cristina; Riva, Giuseppe (Frontiers in Psychology, 2019)
In the last decades, emotion regulation (ER) received increasing attention and became one of the most studied topics within the psychological field. Nevertheless, this construct has not been fully updated with the latest technological advancements. In this perspective, we will show how diverse technologies, such as virtual reality (VR), wearable biosensors, smartphones or biofeedback techniques, can be applied to the understanding, assessment and intervention of ER, both at an individual and integrative level. After providing a brief overview of the currently available technological developments, we will discuss the benefits of incorporating new technologies in ER field, including ecological validity, intervention personalization and the integration of understudied facets of ER, such as the implicit and interpersonal dimension.